Sturm-Liouville systems are Riesz-spectral systems - Delattre, Cédric; Dochain, Denis; Winkin, Joseph (Zielona Góra: Uniwersytet Zielonogórski)
The class of Sturm-Liouville systems is defined.
Keywords: Sturm-Liouville system; Riesz-spectral system; infinite-dimensional state-space system